Acute effects of exercise on appetite, ad libitum energy intake and appetite-regulatory hormones in lean and overweight/obese men and women - Douglas, J A (Int J Obes (Lond), 2017)
BACKGROUND: Acute exercise does not elicit compensatory changes in appetite parameters in lean individuals; however, less is known about responses in overweight individuals. This study compared the acute effects of moderate-intensity exercise on appetite, energy intake and appetite-regulatory hormones in lean and overweight/obese individuals. METHODS: Forty-seven healthy lean (n=22, 11 females; mean (s.d.) 37.5 (15.2) years; 22.4 (1.5) kg m(−2)) and overweight/obese (n=25, 11 females; 45.0 (12.4) years, 29.2 (2.9) kg m(−2)) individuals completed two, 8 h trials (exercise and control). In the exercise trial, participants completed 60 min treadmill exercise (59 (4)% peak oxygen uptake) at 0–1 h and rested thereafter while participants rested throughout the control trial. Appetite ratings and concentrations of acylated ghrelin, peptide YY (PYY) and glucagon-like peptide-1 (GLP-1) were measured at predetermined intervals. Standardised meals were consumed at 1.5 and 4 h and an ad libitum buffet meal was provided at 7 h. RESULTS: Exercise suppressed appetite (95% confidence interval (CI) −3.1 to −0.5 mm, P=0.01), and elevated delta PYY (95% CI 10 to 17 pg ml(−1), P<0.001) and GLP-1 (95% CI 7 to 10 pmol l(−1), P<0.001) concentrations. Delta acylated ghrelin concentrations (95% CI −5 to 3 pg ml(−1), P=0.76) and ad libitum energy intake (95% CI −391 to 346 kJ, P=0.90) were similar between trials. Subjective and hormonal appetite parameters and ad libitum energy intake were similar between lean and overweight/obese individuals (P⩾0.27). The exercise-induced elevation in delta GLP-1 was greater in overweight/obese individuals (trial-by-group interaction P=0.01), whereas lean individuals exhibited a greater exercise-induced increase in delta PYY (trial-by-group interaction P<0.001). CONCLUSIONS: Acute moderate-intensity exercise transiently suppressed appetite and increased PYY and GLP-1 in the hours after exercise without stimulating compensatory changes in appetite in lean or overweight/obese individuals. These findings underscore the ability of exercise to induce a short-term energy deficit without any compensatory effects on appetite regardless of weight status.